(untitled) (Development Service Industry Management, 2024)
Today’s digital marketing is undergoing significant changes due to digital transformation. The article explores the key trends shaping the modern digital marketing paradigm, including process automation, content personalization, the use of big data, as well as the latest digital technologies such as VR and AR, artificial intelligence. The article pays special attention to the challenges and opportunities that companies face in the process of adapting to the digital environment. The article analyzes modern digital marketing tools. Today’s digital marketing tools are essential for any business because they allow you to reach your target audience through a variety of digital channels. They provide effective interaction with customers, including personalization of communications and offers. During the study, the practical aspects of the integration of digital technologies into marketing activity with the aim of increasing its efficiency and effectiveness were determined. Modern digital marketing trends play a primary role in the development of a company’s digital marketing strategy. A digital marketing strategy allows you to respond more quickly to changes in the market and adapt to new conditions, which ensures the sustainable development of the company in the conditions of the digital economy. In today’s world, where digital transformation is transforming business processes and consumer habits, digital marketing is becoming a necessity for businesses in all sectors of the digital economy. An analysis of modern digital marketing trends demonstrates that automation strategies, the use of big data, personalization of content and the introduction of the latest technologies are critical for successful competition and attracting the modern consumer. Modern digital marketing tools are analyzed, the advantages of the development of digital tools in the context of digital marketing are determined and substantiated, practical aspects of the integration of the latest technologies in marketing activities are proposed to increase their effectiveness and efficiency. The integration of digital technologies and tools allows companies to quickly adapt to changing market conditions and remain competitive. This contributes to the creation of more flexible, adaptive and personalized marketing strategies that meet the modern needs of consumers. The results of the conducted studies emphasize the importance of constant improvement of marketing strategies and adaptation to rapidly changing market conditions to effectively use the potential of digital tools in marketing activities.